Relationships among foreign aid, foreign direct investment, and economic growth in East African community members - Albiman, Masoud Mohammed (2013)
This study has been conducted on a selected sample of EAC members, namely Kenya,Uganda, Rwanda, and Burundi. The study has two main objectives, first being to examine the role of foreign aid in economic growth in the long run, and their interaction in the short run. Second objective is to examine the role of foreign aid (bilateral and multilateral) in FDI inflows in the long run, and their interaction in the short run. In achieving these objectives, the study utilized endogenous growth model originated from neoclassical growth theories. To accomplish these objectives, the study used Dynamic Ordinary Least Square (DOLS) and Vector Error Correction model (VECM).DOLS method is more suitable in cases which there are serial correlation and a small sample size. The study found that, in the long run FDI has significant positive impact on economic growth for Kenya and Burundi. On the other hand, the impact is negative for Uganda. In the short run, the study found that, FDI has no impact on economic growth for all EAC members. However, the study revealed that, in the short run, increase in FDI enhances more foreign aid inflows in Rwanda; whilst in Burundi FDI promotes domestic investment. The study also found that, in the long run, export does not have any impact on economic growth Kenya, Uganda and Rwanda. However, in Burundi, export has a positive and significant role in economic growth. Moreover, in the short run, the results suggest that, export does not have any impact on economic growth for three EAC members out of four. The only impact is found in Uganda, where export granger causes economic growth. Furthermore, for the case of foreign aid we found that, in the long run it has a positive and significant impact of economic growth for Kenya and Burundi. In contrast, we found the negative and significant impact of foreign aid on economic growth of Uganda. On the other hand, in the short run, the results suggest that, foreign aid causes economic growth and domestic investment in Uganda. Furthermore, we found that, an increase in foreign aid causes increase in exports in Kenya whilst, in Burundi foreign aid promotes domestic investment. However, this impact failed to interact with the economic growth in either country. According to the results, it is worthwhile to form appropriate policies that will ensure positive impact of FDI on economic growth for all EAC members in the long run and the short run. On the other hand, major policies to improve export performances and ensuring a positive impact on economic growth have to be reformed. Furthermore, it is worthwhile to reform policies so that, foreign aid would have a sustainable positive impact on economic growth. For the second objective, the impact of bilateral aid in the long run is negative in the case of Rwanda and positive for Uganda. On the other hand, in the short run bilateral aid does not have any impact on FDI for any countries. In the long run, multilateral aid has significant positive and negative impact on Rwanda and Burundi respectively. Furthermore, results suggest that, multilateral aid has no impact to FDI inflows in Uganda and Kenya. Not only that, but also, in the short run, multilateral aid has no impact to FDI for any EAC members. In general, to enhance FDI inflows, Rwanda and Burundi have to encourage more multilateral aid whilst Uganda, has to encourage more bilateral aid.